Ebselen and cytokine-induced nitric oxide synthase expression in insulin-producing cells - De-Mello, Maria A. R. [UNESP]; Flodström, Malin; Eizirik Decio L., Decio L. (Elsevier, 1996)
Interleukin-1 (IL-1) may be a mediator of β-cell damage in insulin-dependent diabetes mellitus (IDDM). The IL-1 mechanism of action on insulin-producing cells probably includes activation of the transcription nuclear factor κB (NF-κB), increased transcription of the inducible form of nitric oxide synthase (iNOS) and the subsequent production of nitric oxide (NO). Reactive oxygen intermediates, particularly H2O2, have been proposed as second messengers for NF-κB activation. In the present study, we tested whether ebselen (2-phenyl-1,2-benzisoselenazol-3(2H)-one), a glutathione peroxidase mimicking compound, could counteract the effects of IL-1β, H2O2 and alloxan in rat pancreatic islets and in the rat insulinoma cell line RINm5F (RIN cells). Some of these experiments were also reproduced in human pancreatic islets. Ebselen (20 μM) prevented the increase in nitrite production by rat islets exposed to IL-1β for 6 hr and induced significant protection against the acute inhibitory effects of alloxan or H2O2 exposure, as judged by the preserved glucose oxidation rates. However, ebselen failed to prevent the increase in nitrite production and the decrease in glucose oxidation and insulin release by rat islets exposed to IL-1β for 24 hr. Ebselen prevented the increase in nitrite production by human islets exposed for 14 hr to a combination of cytokines (IL-1β, tumor necrosis factor-α and interferon-γ). In RIN cells, ebselen counteracted both the expression of iNOS mRNA and the increase in nitrite production induced by 6 hr exposure to IL-β but failed to block IL-1β-induced iNOS expression following 24 hr exposure to the cytokine. Moreover, ebselen did not prevent IL-1β-induced NF-κB activation. As a whole, these data indicate that ebselen partially counteracts cytokine-induced NOS activation in pancreatic β-cells, an effect not associated with inhibition of NF-κB activation.
Keywords: ebselen; hydrogen peroxide; insulin-dependent diabetes mellitus; interleukin-β; nitric oxide; pancreatic islets; alloxan; cytokine; glucose; immunoglobulin enhancer binding protein; insulin; nitric oxide synthase; nitrite; reactive oxygen metabolite; recombinant gamma interferon; recombinant interleukin 1beta; recombinant tumor necrosis factor alpha; animal cell; animal tissue; cancer cell culture; cell protection; controlled study; drug antagonism; enzyme induction; glucose oxidation; human; human tissue; insulin dependent diabetes mellitus; insulin release; insulinoma; male; mediator; nonhuman; pancreas islet beta cell; priority journal; protein expression; rat; second messenger; Alloxan; Animals; Antioxidants; Azoles; Cytokines; Humans; Hydrogen Peroxide; Insulin; Insulinoma; Interleukin-1; Islets of Langerhans; Male; NF-kappa B; Nitric Oxide Synthase; Organoselenium Compounds; Pancreatic Neoplasms; Rats; Rats, Sprague-Dawley